Is the alcopops tax working? Probably yes but there is a bigger picture. - Skov, S.; Chikritzhs, Tanya; Kypri, K.; Miller, P.; Hall, W.; Daube, Mike; Moodie, R. (Australasian Medical Publishing Company Pty. Ltd., 2011)
The Australian Government's decision to raise taxes on ready-to-drink spirit-based beverages (RTDs; "alcopops") in 2008 caused great controversy. Interest groups have selectively cited evidence to support their points of view. The alcohol industry cited Victorian data from the Australian Secondary Students' Alcohol and Drug Survey (ASSADS) as evidence that the tax had failed, but closer examination of the data suggests that fewer students are drinking, and fewer are drinking at risky or high-risk levels. Excise data from the first full year after the tax came into effect showed a more than 30% reduction in RTD sales and a 1.5% reduction in total pure alcohol sold in Australia. Although understanding the impact of the alcopops tax will require critical analysis of a range of evidence, sales and ASSADS data suggest that the tax has resulted in reduced consumption of RTDs and total alcohol. The most effective and cost-effective measures for reducing consumption and harm are a comprehensive graduated volumetric alcohol taxation system, a minimum price per standard drink, and special measures for particular products that may cause disproportionate harm. While welcoming the alcopops tax, public health advocates have consistently argued for a comprehensive package ofreform that covers pricing, availability and promotion of alcohol, as well as education and treatment services. MJA 2011: 195.